MENTAL READINESS OF MUHAMMADIYAH TEACHERS TO ENTER THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Sukirman, Sukirman; Hidayati, Dian (Universitas Pendidikan Indonesia, 2024)
This study aims to analyze the factors that influence the mental readiness of Muhammadiyah teachers in entering or facing the era of the industrial revolution 4.0. This study uses a quantitative approach involving 60 respondents from 5 Junior High Schools (SMP) in the Special Region of Yogyakarta. Data were taken using a questionnaire and analyzed using a regression test. The results of the study indicate that the mental readiness of Muhammadiyah teachers in entering or facing the era of the industrial revolution 4.0 is influenced by the behavioral readiness and health readiness possessed by the Muhammadiyah teachers. The significance value of the influence of behavioral readiness on the mental readiness of teachers is 0.019; while the significance value of the influence of health readiness on the mental readiness of Muhammadiyah teachers in facing the era of the industrial revolution 4.0 is 0.040.